BAITUL MAL WAT TANWIL DAN KESEJAHTERAAN MASYARAKAT DI KELURAHAN CIMINCRANG BANDUNG - Adnani, Latifah; Kania, Trisa Nur (Universitas Ahmad Dahlan, 2019)
Most of the Cimincrang people originally came from their own fields. In connection with the development of areas that make Cimincrang residents their land must be sold to the government and housing developers because the Cimincrang area will be the center of the administration of the City of Bandung 2 primary and commercial area, so residents can no longer run the agricultural sector. Many residents who turn jobs become traders, motorcycle taxis driver, factory workers, casual daily workers. Due to the increasing needs of the community while the ability of citizens is limited, so to meet their daily needs and to increase business capital, many of them use the services of loan sharks whose loan repayments are considered burdensome. This condition prompted several community leaders in the Cimincrang region to hold a meeting to establish Baitul Mal wat Tamwil Insan Madani (Iman), a microfinance institution helping the people in the economic sector. The purpose of this study is to determine the role of Baitul Mal wat Tamwil (BMT), the welfare of the community in Cimincrang Village, Bandung, and the role of BMT in improving the welfare of the community in Cimincrang Village, Bandung. This study uses a qualitative approach with descriptive methods. Based on the research results, the residents of CimincrangÂ Urban Village were greatly helped by the presence of the BMT Faith, becauseÂ they have not been in debt with loan sharks anymore, and funds from BMT areÂ not difficult to obtain, basically trust.